ESTETIKA TARI LEGONG SEBUAH IDENTITAS TARI BALI - Ni Made Pira Erawati (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
Legong dance as a legacy of Balinese cultural arts, has a long history, from very simple to complex forms. As a result of artistic creativity, legong dance comes with a high aesthetic concept so that it is used as a reference in every work on Balinese dance. Thus the paper aims to reveal the aesthetic concept of the Legong dance which is considered to represent the beauty value of Balinese dance. It can be understood that every dance performance, even though there is no legong dance, is known by the audience as “mebalih” (watching) legong. Based on the above objectives, several problems arise, what is the aesthetic concept, legong dance and what are the elements that make up the aesthetic of the legong dance. Legong dance is a work of dance that is proud of by the community as the identity of Balinese dance. As an identity, the legong dance has been admired by the Balinese people from time to time, so it is placed as a symbol of Balinese dance. In accordance with the problems in this paper, the object of study is the aesthetic concept of the legong dance and the main elements of the Legong dance. To explain the problems being studied, qualitative research methods can be used by emphasizing field research (grounded reaserch) which is analyzed by aesthetic theory and identity theory. The results of this paper will be able to explain the meaning of Legong dance aesthetics, which is built from elements of motion, appearance and story. These elements are present as one unit in the form of the lagong dance.